People's mining governance and ecological impacts in Jayapura City (1998-2024) - Hotlan Samosir; Tiurlina Siregar; Yansen Alberth Reba; M. Zaenul Muttaqin; Fakhar Hussain; Rendra Christian Samosir (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: The case of artisanal mining in Jayapura City has had positive socioeconomic impacts through job creation. However, it has also raised concerns about ecological impacts, including landscape degradation and contamination of the watershed that drains into Lake Sentani. Purpose/Study Objectives: This study aims to analyze the dynamics of community mining governance in Jayapura City since 1998, with a focus on the role of local government in law enforcement and the ecological impacts of small-scale gold mining activities. Design/Methodology/Approach: A socio-legal research approach was adopted, grounded in an empirical-juridical paradigm to capture both the statutory framework and its practical implementation. Data for the study were compiled through an analysis of regulatory documents, academic literature, and environmental impact reports, augmented by systematic field observations at key mining sites around Jayapura (including buffer zones near the Cyclops Nature Reserve and the Lake Sentani watershed). Observations were conducted over five months, utilizing document research protocols and peer review verification to ensure data reliability and analytical rigor. Findings: The findings reveal regulatory gaps and weak law enforcement, resulting in rampant illegal mining and environmental degradation, including land degradation, alterations to the hydrological system, and pollution of the watershed, ultimately affecting Lake Sentani. Although formalization of community mining businesses was attempted after 2007, challenges such as weak coordination between agencies, limited oversight, and conflicts of interest complicate the implementation of sustainable regulations. This study recommends strengthening the assessment of community mining areas, developing transparent local regulations, improving oversight and law enforcement mechanisms, and involving communities in environmental monitoring and advocacy to achieve a balance between regional economic and environmental sustainability. Paper Type: Research Article